THE ROLE OF SHARIA BANK IN THE DEVELOPMENT OF THE ISLAMIC ECONOMY IN SOUTH SULAWESI - Nurfadhila Nurfadhila; Azizka Ramadani; Amirul Syam Fadil; Kamaruddin Kamaruddin (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2025)
Sharia banks play a very important role in the development of the Islamic economy, especially in areas where the majority of the population is Muslim, such as South Sulawesi. In this context, Islamic banks not only function as financial institutions, but also as drivers of economic growth based on fairsharia principles and in accordance with Islamic teachings. This article aims to analyze the role of Islamic banks in advancing the Islamic economy in South Sulawesi, with a focus on aspects of financing micro, small and medium enterprises (MSMEs), sharia investment, and their contribution to community welfare. Using a qualitative approach, this research explores various policies, practices and challenges faced by Islamic banks in developing a regional economy based on Islamic values.